Development of a questionnarie to assess people’s food choices determinants - Ferrão, Ana Cristina (2019)
BACKGROUND: Diet and nutrition are major determinants of public health and are associated with a large number of diseases. Therefore, in order to plan actions to promote global health it is crucial to understand people’s food choices. OBJECTIVE: The aim of this study was the development and validation of a new instrument, a questionnaire to measure psycho-social motivations associated with food choices and eating practices. METHODS: A descriptive cross-sectional study was undertaken on a non-probabilistic sample of 382 adult participants. The questionnaires were applied after informed consent only to adults (aged 18 or over) and the data were collected from January to April 2017 among the Portuguese population. The analysis has been conducted to explore the item-item correlation and the reliability of this new instrument. RESULTS: The results indicated satisfactory correlations between the items of the different variables, except for Variable D (Social and cultural motivations) that did not show strong and significant correlations for almost any items. Considering all the items in each of the variables studied, Cronbach’s alpha values ranged from 0.32 for the marketing and commercial motivations to 0.64 for the economical and availability motivations. When some items were removed from the variables, the values of Cronbach’s alpha increased and ranged from 0.66 for social and cultural motivations to 0.78 for health, environmental and political motivations, and for marketing and commercial motivations. CONCLUSION: This work suggested that this questionnaire could be considered a suitable tool for exploring food choice determinants.